2017
DOI: 10.18632/oncotarget.20210
|View full text |Cite
|
Sign up to set email alerts
|

Maslinic acid promotes autophagy by disrupting the interaction between Bcl2 and Beclin1 in rat pheochromocytoma PC12 cells

Abstract: Maslinic acid (2α, 3β-dihydroxyolean-12-en-28-oic acid, MA) was isolated from natural plants and showed anti-cancer activity in rat Pheochromocytoma PC12 cells in our previous studies. We now discover that MA disrupts the interaction between Bcl2 and autophagy scaffold protein Beclin1 in the above cell line, leading to the up-regulation of autophagy. We investigated the effect of MA on the interaction between Bcl2 and Beclin1 by biochemical and biophysical methods in combination with autophagy characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Furthermore, we confirmed that HET was capable of inducing liver autophagy in the aged FR mice as assessed by the increased number of autophagic vacuoles and significantly increased expression of autophagy-related genes. Although the detailed mechanism underlying the responses to HET is unclear, compounds that increase Beclin1 expression 40 and block the Beclin1–Bcl-2 interaction 43 may contribute to its mechanism of action. Therefore, HET could alleviate the disruption of energy homeostasis during the aging process by mainly inducing liver autophagy, but not anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we confirmed that HET was capable of inducing liver autophagy in the aged FR mice as assessed by the increased number of autophagic vacuoles and significantly increased expression of autophagy-related genes. Although the detailed mechanism underlying the responses to HET is unclear, compounds that increase Beclin1 expression 40 and block the Beclin1–Bcl-2 interaction 43 may contribute to its mechanism of action. Therefore, HET could alleviate the disruption of energy homeostasis during the aging process by mainly inducing liver autophagy, but not anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, most studies focused on the anti-cancer activity of MA, because this compound exerts anti-proliferative and pro-apoptotic effects 2628 . Of interest, doses of more than 100 µM MA have been shown to suppress cell growth and to induce apoptosis, whereas low doses of <100 µM solely affect the proliferation rate of tumor cells 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The sample preparation has been described previously [31]. Briefly, drug-treated HCT 116 cells on coverslips were fixed in freshly-prepared 4% paraformaldehyde, permeabilized with 0.1% Triton X-100, and blocked with 3% BSA (Bovine Serum Albumin, BSA) in PBS (phosphate buffer saline, PBS).…”
Section: Methodsmentioning
confidence: 99%